(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Mining machine equipment plays a crucial role in the mining industry. Its application can be of great benefit to the mining industry and the economy as a whole. Mining machinery equipment is used in various mining operations such as underground mining, open pit mining and surface mining. It is also widely used in mineral exploration, mineral transportation and mineral processing. Mining machinery equipment has made mining operations more efficient and effective. Using advanced technology, mining machines allow for deeper mining and more minerals, which helps to increase the yield of precious minerals. In addition, mining machinery equipment can perform repetitive and dangerous tasks, reducing the risk of human error and injury.